Internal nanoscale architecture and charge carrier dynamics of wide bandgap non-fullerene bulk heterojunction active layers in organic solar cells. Issue 44 (9th November 2020) - Jiang, Xinyu; Kim, Hongwon; Deimel, Peter S.; Chen, Wei; Cao, Wei; Yang, Dan; Yin, Shanshan; Schaffrinna, Roy; Allegretti, Francesco; Barth, Johannes V.; Schwager, Martina; Tang, Haodong; et al.
Abstract : The nanoscale architecture of active layer based on wide bandgap non-fullerene solar cells exhibits pronounced influence by the solvent additive. Abstract : Bulk heterojunction (BHJ) organic solar cells have gained increasing attention in the past few years. In this work, active layers of a wide-bandgap polymer donor with benzodithiophene units PBDB-T-2F and a non-fullerene small molecule acceptor IT-M are assembled into photovoltaic devices with different amounts of solvent additive 1, 8-diiodooctane (DIO). The influence of DIO on the nanoscale film morphology and crystalline structure as well as the charge carrier dynamics of the active layers are investigated by combining grazing-incidence small-angle X-ray scattering (GISAXS), grazing-incidence wide-angle X-ray scattering (GIWAXS), X-ray reflectivity (XRR), UV-visible (UV-vis) absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), time-resolved photoluminescence (TRPL) and space charge limited current measurements, which are correlated with the corresponding performance of the solar cells. At 0.5 vol% DIO addition, the wide-bandgap non-fullerene organic solar cells show the best performance due to high open-circuit voltage and short-circuit current resulting from an improved charge carrier management due to the optimal inner nanoscale morphology of the active layers in terms of surface enrichment, crystallinity and crystalline orientation.